God save the queer: mobilização e resistência Antimainstream no facebook - Nunes, Maira de Souza (2017)
This thesis arises from an articulated participatory experience on the social media Facebook and purposes to think of antimainstream as a politics of estrangement, within which knowledge and power are destabilized by failed utopic resistances.Historically parted from knowledge and power realms, subaltern groups have established resistance and opposition tactics to hierarchies and marginalization, denouncing hegemonic structures that consolidate a mainstream way of life – here understood as a dominant tendency – and establish a normalization system, most of all through media culture. Starting from the notion that technological transformations in the last decades have resulted in forms of decentralized production and sharing of information and in the appearance of different initiatives in antimainstream activism, we have come to the following research problem: To what extent do the friendship, kinship and activism networks, established among subaltern, dissident people and those marked by non-conformity, on Facebook, allow for such articulation of antimainstream subversion and resistance? Searching for answers to this question, we established as a general goal: To analyze antimainstream subjects and movements, from a perspective grounded on feminism, queer and decolonial studies, thinking about their complexities and potentialities as a means of resistance to the status quo. The specific goals of this research were: To build a “state of the art” panorama of the gender and sexuality studies in the field of Communication Studies, highlighting the presence (or absence) of research based on Feminist Theory, as well as Queer and Decolonial Studies; To propose a Theory of the Dominant Tendency, having as its defining aspect the category of mainstream, understood as a hegemonic and heteronormative structure that rules over behaviors and views of the world; To identify the role social media and the internet play on the constitution of the mainstream movement; To investigate the constitution of networks of resistance on Facebook, through a case study of the Slut Walk network of Curitiba. This research was carried out through a transmethodological approach, a “crossbred method” and a “research on research”, comprising the alternation of different procedures: state of the art, history of the concepts, nethnography and self-ethnography. By looking at society from an antimainstream perspective, this research aimed at retrieving something from the experiences of the people who turn their bodies into a battlefield, comprehending that queer presents itself as a will-be, as the possibility of thinking of a new horizon which is not bound by the mainstream frame. Conceiving of queer as a politics of estrangement predicates the creation of possibilities of existence and resistance from new sources and therefore allows us to abandon tolerance, inclusive and belonging discourses, taking on a radical position to face the world